2013
DOI: 10.1155/2013/371034
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Levels and Risk of Parkinson’s Disease in North Indian Population

Abstract: The cause of Parkinson's disease (PD) remains elusive, but environmental chemical exposures have been postulated to be involved in the etiology of PD. We examined the association between the persistent organochlorine pesticides (OCPs) and PD in the North Indian population. This case control study included 70 PD and 75 control subjects in the age group of 50 to 85 years. Blood samples were collected and high-purity grade hexane and acetone (2 : 1 ratio) were used for extraction of organochlorine residues. OCPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Moreover, the patient's exposure was more often to aldrin compared to controls. Another casecontrol study reported that increased dieldrin and β-HCH may be linked with the risk of PD [19]. Furthermore, mice exposed to DDT or DDE failed to show nigrostriatal damage evidence or behavioral abnormalities [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the patient's exposure was more often to aldrin compared to controls. Another casecontrol study reported that increased dieldrin and β-HCH may be linked with the risk of PD [19]. Furthermore, mice exposed to DDT or DDE failed to show nigrostriatal damage evidence or behavioral abnormalities [20].…”
Section: Discussionmentioning
confidence: 99%
“…). Subjects (cases and control) should be in the range of 50‐ to 85‐year age group. Subjects (cases and control) with any gastrointestinal disorder, history of cerebral stroke, epilepsy, head injury and any congenital abnormality should be excluded (Chhillar et al . ). The isolation of genomic DNA from samples followed by bacterial community structure analysis using culture‐independent approaches as mentioned in Table . The use of computational and statistical analysis to investigate changes in bacterial community structures (i.e., to identify the presence or absence of bacterial species) in patients and controls. The isolation and characterization of important bacterial species from the respiratory tract and gut of patients and healthy controls using polyphasic taxonomic approaches. The genome sequencing and annotation of DNA fragments of bacterial species for the identification and characterization of gene(s) that might play role in respiratory tract and gut–bacteria interactions. In addition to bacterial species identification from patients and controls, the metabolomic and metaproteomic analyses are also needed to study for understanding the functional properties of nasopharyngeal and gut microbiota. The use of animal models in the study of the microbiome and imbalance characterized by dysbiosis is needed to be understood which may play essential role in the gut–brain and nasal–brain interactions.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%
“…(b) Subjects (cases and control) should be in the range of 50-to 85-year age group. (c) Subjects (cases and control) with any gastrointestinal disorder, history of cerebral stroke, epilepsy, head injury and any congenital abnormality should be excluded (Chhillar et al 2013).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Organochlorine pesticides (OCP) have been linked with the development of Parkinson"s disease (PD) 57 . Chhillar et al conducted a case controlled study involving 70 PD patients and 75 agematched healthy volunteers found strong association of dieldrin and β-hexachlorocyclohexane with the risk of PD 58 .…”
Section: Groups Of Neurotoxic Agentsmentioning
confidence: 99%